ATRIAL FIBRILLATION: CURRENT PROBLEMS AND PROSPECTS OF MEDICAL CARE, TREATMENT AND PREVENTION - Ju. P. Skirdenko; A. V. Shustov; V. V. Zherebilov; N. A. Nikolaev (Рациональная фармакотерапия в кардиологии)
Modern approaches to antiarrhythmic anti-relapse therapy of atrial fibrillation are considered. Advantages and disadvantages of the main therapeutic strategies are discussed from the standpoint of evidence-based medicine. The value of strategies of rhythm control, heart rate control and «upstream therapy» in the management of patients with atrial fibrillation is specified. Results of clinical studies on the efficacy and safety of anti-arrhythmic drugs, the search for such new drugs are presented. The authors state, that possibilities of modern drug therapy are limited, development and efficiency of other methods of anti-relapse therapy are low, new groups of drugs are not effective enough or are far from clinical applications. At that the adherence to treatment of patients with atrial fibrillation is unstudied, and its influence on the treatment outcomes, prevention of complications and long-term prognosis are ignored. Authors concluded that in conditions of limited capacity for drug therapy, evaluation of the effect of adherence to treatment in patients with atrial fibrillation, and elaboration on this basis the principles and tools of therapy, taking into account social and personal characteristics, are the most perspective directions of modern arrhythmology.